Reviews on Current Carbon Emission Reduction Technologies and Projects and their Feasibilities on Ships - Wang, Haibin; Zhou, Peilin; Wang, Zhongcheng (Journal of marine science and application, 2017)
Concern about global climate change is growing, and many projects and researchers are committed to reducing greenhouse gases from all possible sources. International Maritime Organization (IMO) has set a target of 20% CO2 reduction from shipping by 2020 and also presented a series of carbon emission reduction methods, which are known as Energy Efficiency Design Index (EEDI) and Energy Efficiency Operation Indicator (EEOI). Reviews on carbon emission reduction from all industries indicate that, Carbon Capture and Storage (CCS) is an excellent solution to global warming. In this paper, a comprehensive literature review of EEDI and EEOI and CCS is conducted and involves reviewing current policies, introducing common technologies, and considering their feasibilities for marine activities, mainly shipping. Current projects are also presented in this paper, thereby illustrating that carbon emission reduction has been the subject of attention from all over the world. Two case ship studies indicate the economic feasibility of carbon emission reduction and provide a guide for CCS system application and practical installation on ships.